Social capital under conditions of economic crisis — the example of Southern European countries - Wosiek, Magorzata (Ekonomia i Prawo. Economics and Law, 2016)
Aim: Deliberations of the article revolve around trends of social capital under conditions of economic crisis. Motivation: Final conclusions are based on theoretical considerations and empirical research. The latter include analysis of changes in indicators of social capital (in the cognitive, structural and behavioural dimension) in Southern European countries (Spain, Greece and Portugal) — from comparative perspective — before and after 2007. Data from European Social Survey and European Value Study were used. The example of Southern European countries shows that there can be no universal reaction scheme (in terms of social capital) on the crisis phenomena. Results: A common feature of the analyzed countries after 2007 is an increase in ties with friends (bonding social capital, however the heightened importance may not just be a consequence of the crisis, but rather part of long-term societal change — e.g. Portugal) and a reduction in institutional and systemic trust. It can be also concluded that countries well endowed in social capital (e.g. Spain), in the period of economic crisis to the greater extent employ social capital resources as a response to non-beneficial changes in the economic environment (which is illustrated by higher rates of civic and political participation).